The pharmacokinetic and residue depletion study of eugenol in carp (Cyprinus carpio) - Xu, Yidan; Jiao, Yaqin; Yang, Jian; Tan, Aijuan; Ou, Deyuan; Song, Xuqin; Lv, Shiming (Frontiers in Veterinary Science, 2023)
Introduction The pharmacokinetic profile and residue depletion of eugenol in carp (Cyprinus carpio) tissues and plasma were performed by a convenient and reliable high-performance liquid chromatography (HPLC) method. Methods The eugenol in carp tissues and plasma was extracted with a mixed solution of acetonitrile and methanol. N-hexane was used to remove lipid impurities. The method was successfully applied to the pharmacokinetic and residue elimination of eugenol in carp after the carp was administered a medicated bath. Results The average recoveries of eugenol in tissues and plasma fortified with four concentration levels were 69.0–106.6% and 80.0–86.7%, respectively. The relative standard deviations were < 8.9%. The limit of detection (LOD) was 0.01 μg/g in tissue and 0.008 μg/ml in plasma, respectively. The pharmacokinetic parameter of Cmax for eugenol in plasma at the concentrations of 20, 35, and 75 mg/L were 10.86, 17.21, and 37.32 mg/L, respectively. The t1/2 values were 3.68, 4.22, and 9.31 h. After the investigation of the anesthetic effect, 35 mg/L of eugenol was the optimal concentration for anesthesia. The highest accumulation concentration of eugenol in carp is in the liver and the lowest is in the muscle. In addition, the eugenol in tissue was eliminated rapidly and at a lower level than the LOD at 48 h. According to the residue elimination, the withdrawal time of eugenol was suggested at 5.2 days. Discussion These results indicate that the developed method had good linearity and accuracy, and is sensitive enough for the monitoring of eugenol residue in carp. The half-life of eugenol decreased with the increase in drug concentration and the eugenol was eliminated rapidly in carp tissues. 35 mg/L eugenol was recommended as an anesthetic in carp due to its favorable anesthetic effect and no mortality. This study will contribute to the establishment of MRL regulation and setting a withdrawal period.